The Effect of Using Controlled Writing Technique and Clustering Technique on Students’ Writing Skills at Junior High School - Erika Sinambela; Dorayanti Lumban Gaol; Sahlan Tampubolon; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study deals with the effect of using controlled writing technique and clustering technique on students’ writing skill. This study used an experimental quantitative research that incriminating three classes were experimental 1 class, experimental 2 class and control class, in the experimental class the writer applied controlled writing technique and Clustering technique while in controlled class applied conventional technique. The populations of this study were the students’ class of VII of SMP St. Ignasius Medan. The researcher used 75 students as the sample. The sample of this research was taken by using random sampling technique, 25 from VII-1 and 25 VII-2 as experimental class and 25 from VII-3 as controlled class. To obtain the data the researcher used writing test, as the instrument for collecting the data. These test consisted of two types, namely pre-test and post-test. As the result of the ANOVA test, P= 0.000 < 0.05 or F count = 23.40 > F table = 2.28 significant affect. It means that hypothesis alternative (Ha) was accepted while the null hypothesis (H0) was rejected. The experimental class 1 and 2 scored higher than the control class, according to the results of the study. Controlled writing technique and clustering technique are both successful in boosting writing descriptive text, according to the result. The statistics also indicate that the clustering technique outperforms the controlled writing technique.